Lo sagrado en lo cotidiano: una nota de onomástica manzoniana - Barbolani, Cristina (Cuadernos de Filología Italiana, 2010)
This paper is a short approach to the use of the name “Maria” in Manzoni’s masterpiece, focused in connection with one of the first Inni sacri just addressed to the liturgical celebration of the Virgin’s name.
Keywords: Manzoni; Anthroponomastics; Catholicism; Sacred oratory; Devoutness